Seorang Pria 21 Tahun dengan Urin Berwarna Gelap - Joseph Partogi Sibarani (Nommensen Journal of Medicine, 2019)
First published by Strubing in 1882, Paroxysmal Nocturnal Hemoglobinuria (PNH) is a chronic acquired disorder characterized by the occurrence of intravascular hemolysis and hemoglobinuria which commonly occurs when patients sleep at night, caused by cellular abnormalities due to somatic mutations that cause intrinsic damage on the red blood cell membrane, making it more susceptible to complement lysis. The incidence of PNH varies greatly in various populations and is more common in Southeast Asia. In general, the incidence is estimated to be 1 -1.5 cases / million population. This case is more common in young adults, but can also be found in children and parents. In general the clinical picture of PNH includes symptoms of anemia, hemoglobinia, signs of bleeding, and gastrointestinal complaints. Diagnosis can be determined through blood, urine, bone marrow and cytogenetic examination. We reported the case of a 21-year-old man with complaints of pale face, easy fatigue and tea colored urine in the morning. After several laboratory tests and aspiration of the bone marrow, PNH diagnosis is made. Glucocorticoids used as therapy, and patients are discharged with clinical improvement.